ANALISIS YURIDIS KEKUATAN P EMBUKTIAN KETERANGAN SAKSI TESTIMONIUM DE AUDITU PASCA LAHIRNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR : 65/PUU-VIII/2010 - Namira Delima; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Decision of the Constitutional Court No. 65 / PUU-VIII / 2010concerning Testing of Law Number 8 of 1981 concerning Criminal ProcedureLaw, provides an extension of the understanding of witnesses stipulated in article1 points 26 and 27 of the Criminal Procedure Code. The Constitutional Court asone of the judicial power institutions whose decisions are final and binding, canbe one of the sources of criminal procedural law in Indonesia. But in practicethere are still many judges who do not follow the Constitutional Court Decisionas one of the instruments of evidence of legitimate witnesses in court. The purposeof writing this thesis is, first: To find out the strength of the testimony of thetestimonium de auditu's testimony after the birth of the Constitutional CourtDecision Number: 65 / PUU-VIII / 2010. Second: To find out the implications ofthe Constitutional Court Decision Number: 65 / PUU-VIII / 2010 on thetestimonies of witnesses of the testimonium de auditu in the decision of thecriminal court.This type of research is normative juridical research, namely researchcarried out by examining literature with secondary data sources consisting ofprimary legal material in the form of legislation, secondary legal material legalbooks, and tertiary legal materials in the form of dictionaries. Then the data areanalyzed qualitatively, namely analyzing data descriptively obtained fromsecondary data.From the results of the study it can be concluded that, first, the strengthof the testimony of the testimonium de auditu's testimony after the birth of theConstitutional Court Decision Number: 65 / PUU-VIII / 2010 is that testimony oftestimonium de auditu can be used as a valid evidence in a trial at a criminalcourt case . second, the implication of the Constitutional Court Decision Number:65 / PUU-VIII / 2010 on the testimony of the witness of the testimonium de auditin the verdict of the criminal court is to make the Constitutional Court DecisionNumber: 65 / PUU-VIII / 2010 need to be followed and considered in every courtdecision.Keywords: Evidence Tools - Witness Information - Testimonium De Auditu -Decision of the Constitutional Court